Anthropogenic activities impact on water quality, fish community and bacteria presence in disturbed and undisturbed North Selangor Peat Swamp Forest, Malaysia - Aliu, Sule Hussein (2016)
This study is concerned with the impact of anthropogenic activities on the water quality, the fish community and the bacteria presence in disturbed and undisturbed north Selangor peat swamp forest (NSPSF). Field sampling and analyses were conducted during the months of June and October 2015, and January 2016. Environmental conditions, and water physicochemical data were measured in peat swamp, paddy field and oil palm plantation. Fish was collected and bacterial isolation and identification from fish, water and sediment using standard microbiological techniques. Statistical analyses employed include ANOVA and Turkey LSD, Kruskal-Wallis and Mann- Whitney tests, Principal Component Analysis (PCA) and Canonical Correspondence Analysis (CCA). In addition, fish community structure was calculated using Shannon- Weaver diversity, Pielou’s evenness and Margalef’s richness indexes. Peat swamp recorded a significantly (p < 0.05) higher phosphate (1.937 ± 0.196 mg L- 1), sulphate (28.917 ± 20.398 mg L-1) and chlorine (0.915 ± 0.361 mg L-1), while low for pH (3.684 ± 0.251), dissolved oxygen (0.590 ± 0.169 mg L-1) and ammonia-nitrogen (0.346 ± 0.081 mg L-1) when compared to paddy field and oil palm plantation areas. However, there was no significant (p > 0.05) difference observed for water electrical conductivity, total dissolved solids, salinity and nitrite for at least two of the sampling habitats, and for all of the sampling habitats for water temperature. The phosphate and chlorine levels of all sites, the pH of peat swamp (3.684 ± 0.251) and paddy field (4.962 ± 0.462), and the dissolved oxygen level in peat swamps were above the standard level for support of aquatic life and fall into class V of the National Water Quality Standard (NWQS) of Malaysia. Paddy field recorded a significantly (p < 0.05) lower score of accessibility (1.50 ± 0.548) and deforestation level (1.00 ± 0.000), while oil palm recorded the lowest score of pollution level (2.00 ± 0.000). There was no significant (p > 0.05) difference on level of human development, water depth and pollution in at least two of the sampling habitats, and for all of the sampling habitats in term of the distance from human settlement. With the exception of water depth, all of the measured environmental conditions showed their importance in determining the water quality of the NSPSF. Statistical analyses revealed that pollution level is the most important environmental factor determining water quality in the NSPSF. A total of 1382 individual fish belonging to 20 species were collected during this study. Of this, only 15 species were collected from peat swamp, compared to 19 and 20 species from paddy field and oil palm plantation respectively. In the same vein, peat swamp recorded the lowest species diversity (2.4243) and richness (2.4768), compared to paddy field and oil palm plantation. Family Cyprinidae has the highest number of representative species. A notable concern however is the absence of several endangered species such as Betta livida and Parosphromenus harveyi, which were previously recorded from the NSPSF, highlighting the need for a reassessment of their conservation status. Multivariate statistics reveal that the water physicochemical parameters such as water temperature, conductivity, ammonia, sulphate, chlorine and dissolved oxygen influence fish community. A total of 3,421 isolates from 39 species of bacteria were obtained during this study. The most dominant bacterial species were Escherichia coli, Salmonella spp., and Streptococcus agalactiae. Paddy field and oil palm plantation had the highest number of isolates and species, due to higher anthropogenic inputs in these areas. Among the species isolated were several pathogens such as Aeromonas hydrophila, Edwardsiella tarda, Staphylococcus spp., and S. agalactiae. Water physicochemical parameters such as water temperature, conductivity, ammonia, sulphate, chlorine and dissolved oxygen were important in influencing bacterial composition. This study identifies peat land conversion to agriculture, anthropogenic inputs such as domestic and industrial effluents discharge as the greatest threats to the resident biological communities in the NSPSF. Among others, the importance of inclusion of water quality improvement strategies in peatland conservation was highlighted.